Unveiling the Balkans’ advances: In vitro biotechnology of woody plants in the early 21st century - Sota, Valbona; Nacheva, Lilyana; Bošnjak, Dejan; Abraham, Eleni; Jevremović, Slađana; Cvjetković, Branislav; Galović, Vladislava; Jevremović, Darko; Marković, Zvjezdana; Kongjika, Efigjeni; Bogunović, Sanja; Zeljković, Svjetlana; et al. (Frontiers in Plant Science, 2025)
The Balkan Peninsula is a European biodiversity hotspot, home to 6,500 native vascular plant species, many of which are endemic. The region has diverse range of climates and complex topography, creating conditions that suit many woody ornamental, fruit, and forest species. Nevertheless, climate change, habitat destruction, invasive species, plant diseases, and agricultural practices threaten natural ecosystems and cultivated species. Many Balkan countries have addressed these challenges using advanced biotechnological approaches, including micropropagation, in vitro conservation, and in vitro selection for stress-tolerant genotypes. This paper provides a comprehensive overview of in vitro plant biotechnology progress in the Balkan countries from the beginning of the 21st century to the present, with a focus on woody horticultural and forest species. The primary objectives of scientific research include optimizing media composition for all components and micropropagation stages, as well as effective initial explant selection. In addition, temporary immersion bioreactors, synthetic seed technology, and cryopreservation techniques have been explored to enhance plant production and conservation. Scientific research for woody ornamentals and fruit tree species has progressed in Albania, Bulgaria, Croatia, Greece, and Serbia while remaining limited in other Balkan countries. Forest tree production research is currently conducted in Bulgaria, Greece, and Serbia, with labs focusing on micropropagation and ex situ conservation. In addition to advances in scientific research, several commercial companies operate in the Balkans, with establishments in Serbia, Greece, Bulgaria, and North Macedonia, that produce in vitro-derived planting material for fruit trees and woody ornamental plants. Despite this progress, research in the Balkan countries remains fragmented, emphasizing the need to strengthen regional collaboration and knowledge exchange to promote agricultural development processes and biotechnological applications in this region. This review represents the first exploration of this topic in the Balkans and successfully unites researchers from several countries. It highlights key scientific advances in in vitro biotechnology for woody plants, identifies challenges, and proposes solutions. The value of interdisciplinary collaboration is emphasized through the optimization of in vitro methodologies, the promotion of germplasm conservation, and the sustainable use of plant genetic resources in the Balkans.